Evaluation of analgesic activity of hydrocotyle conferta wight (apiaceae) - an endangered plant species in the Southern western ghats of india - R. NANTHA KUMAR; H. L. JEMIMMA; K. ARUMUGASAMY; H. ABDUL KAFFOOR (International Journal of Pharma and Bio Sciences, 2018)
A medicinal plant has been established as an important basis of medicine since immemorial past. The genus Hydrocotyle of Apiaceae consists of more than 75 to 100 species. Hydrocotyle conferta is a climbing prostrate herb and it is generally found growing in high altitude slopes in montane tropical forests and near streams. These areas are highly threatened due to various anthropogenic pressures that potentially have a major impact on the survival of this plant species. It was evaluated for analgesic activity by eddys hot plate method and heat conduction method on male albino rats. The crude whole plant methanolic extract was used at the doses of 100, 200, and 400 mg/kg. Diclofenac sodium was used as the standard drug. H. conferta could be alternately used in the treatment of analgesic activity.